2004
DOI: 10.1007/s00464-003-4262-5
|View full text |Cite
|
Sign up to set email alerts
|

Right hepatic artery pseudoaneurysm and cystic duct leak after laparoscopic cholecystectom

Abstract: Laparoscopic cholecystectomy (LC) seems to be associated with an increased risk of biliary or vascular injuries. Hepatic artery pseudoaneurysms (HAP) are rare complications of LC. HAP can occur in the early or late postoperative period. Patients with HAP present with abdominal pain, hemobilia, and liver function test (LFT) alterations. We report the case of a patient who was affected with a cystic duct stump leak associated with a right HAP and was treated by endoscopic biliary drainage and angiographic coil e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…Therefore, it is used increasingly in the treatment of patients with gallstone disease. The overall complication rate reaches 5.1% and includes cystic duct leakage, biliary obstruction, or late onset stricture caused by partial or complete hepatic or common duct ligation, retained cystic/bile duct stones, right hepatic artery pseudoaneurysm, and malposition of T-tubes in the remnant [1,5,12,14]. Postlaparoscopic bile duct injury is of important morbidity related partly to unrecognized anatomic variants of extrahepatic bile duct and cystic duct.…”
mentioning
confidence: 97%
“…Therefore, it is used increasingly in the treatment of patients with gallstone disease. The overall complication rate reaches 5.1% and includes cystic duct leakage, biliary obstruction, or late onset stricture caused by partial or complete hepatic or common duct ligation, retained cystic/bile duct stones, right hepatic artery pseudoaneurysm, and malposition of T-tubes in the remnant [1,5,12,14]. Postlaparoscopic bile duct injury is of important morbidity related partly to unrecognized anatomic variants of extrahepatic bile duct and cystic duct.…”
mentioning
confidence: 97%
“…Some authors have suggested that it may result from direct trauma to the vessel wall or a diathermy shorting of the surgical clip at the cystic artery stump. 2,12 Another author has suggested that it may result from a postoperative bile leak with subsequent infl ammation and erosion of the vessel wall. 9,11 We hypothesize that in our case, direct trauma of the vessel wall occurred during the dissection of the cystic artery at the infl amed Calot's triangle with subsequent PA formation.…”
Section: Discussionmentioning
confidence: 98%
“…Most cases of PA were embolized successfully using a transcatheter (84.6%), and some reports suggested that packing the hepatic artery PA sack with metal coils is an appropriate treatment. 11,12 However, a reruptured PA has also been reported after embolization requiring emergency surgical hepatic artery ligation or further embolization. 3,7,8,10 The recent surgical repair may be disrupted, and it is surgically diffi cult to gain a proximal and distal control of bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Most of these bleeds occur after leakage of an anastomosis with secondary inflammation and pseudoaneurysm formation. [39][40][41] For haemodynamically stable patients upper GI endoscopy is the first diagnostic procedure to exclude the more common upper GI bleedings (see above).…”
Section: Hpb Bleedingmentioning
confidence: 99%